A new Comanthera (Eriocaulaceae) from the Espinhaço Range, Minas Gerais, Brazil - Echternacht, Livia; Sano, Paulo Takeo (Brittonia, 2012)
We describe and illustrate the new species Comanthera brunnea (Eriocaulaceae: Paepalanthoideae). This species is endemic to the sandy fields of the campos rupestres of the northeastern Espinhaço range in Minas Gerais, Brazil. We compare it with Comanthera suberosa, the morphologically most similar species, and with C. brasiliana, which also has similar features. The morphological variation, habitat, geographic distribution, and conservation status of this new species are discussed. Descrevemos e ilustramos a nova espécie Comanthera brunnea (Eriocaulaceae: Paepalanthoideae). Esta espécie é endêmica dos campos rupestres arenosos da porção nordeste da Cadeia do Espinhaço em Minas Gerais, Brasil. Comparamos esta espécie com Comanthera. suberosa, a espécies mais similar morfologicamente, e com C. brasiliana, que também apresenta características em comum. Fazemos comentários sobre a variação morfológica, habitat, distribuição geográfica e status de conservação.